2021
DOI: 10.7717/peerj.12580
|View full text |Cite
|
Sign up to set email alerts
|

Change in alcohol consumption and physical activity during the COVID-19 pandemic amongst 76 medical students

Abstract: Objective To investigate whether the COVID-19 pandemic has affected physical activity and alcohol consumption among medical students. Methods Cross-sectional survey study among 76 students in their second year of medical school. The Wilcoxon sign-rank test and Kruskal-Wallis H test were used to assess the difference between groups. Results Of 76 respondents, 68% were women, 66% were single and 34% were co-habiting. The median age was 21 years. Overall alcohol consumption decreased during the pandemic year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…7,11,12,14,16,18,20,24,25,28,35,36 Fifteen studies reported a decrease in people’s time doing PA during the COVID-19 pandemic: Bertrand et al 16 reported a decrease in time spent in moderate-vigorous PA per week from 85 min before to 65 min during the pandemic; these results are similar to those reported in other 14 studies. 8,9,15,19,22,26,28-31,33,35,37,38…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7,11,12,14,16,18,20,24,25,28,35,36 Fifteen studies reported a decrease in people’s time doing PA during the COVID-19 pandemic: Bertrand et al 16 reported a decrease in time spent in moderate-vigorous PA per week from 85 min before to 65 min during the pandemic; these results are similar to those reported in other 14 studies. 8,9,15,19,22,26,28-31,33,35,37,38…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the articles are presented in Table 1. We included 28 cross-sectional studies 7,8,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][33][34][35][36][37][38] ,4 longitudinal studies. 9,11,25,32 There is one global study, 38 and 2 or more studies covered different countries: 2 from Saudi Arabia., 7,24 5 from Spain 10,25,33,34,36 ,4 from USA 11,14,27,29 ,2 from the UK 17,32 ,3 from Italy, 20,26,37 and 2 from China.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, our results appear to be consistent with some past studies, where a significant reduction in physical activity was seen in the medical student body ( 37 39 ). Other studies report physical activity levels were not significantly impacted by the pandemic, suggesting that more available time and medical students being more likely to pursue healthy behaviors to be possible explanations ( 40 , 41 ). However, it is important to note that prevalence of low physical activity was initially high in one of the aforementioned studies ( 40 ).…”
Section: Discussionmentioning
confidence: 95%